1994
DOI: 10.1002/zoo.1430130408
|View full text |Cite
|
Sign up to set email alerts
|

Masturbation in captive Hylobates (gibbons)

Abstract: Masturbation was observed in 9 of 52 captive adult Hylobates (gibbons) over a period of 17 years at the International Center for Gibbon Studies (ICGS). Four females and 5 males masturbated with varying degrees of regularity. The behavior may be related to a disruption in early rearing experiences of Hylobates. This is the first report on masturbation in these animals and documents that this behavior occurs infrequently in captive Hylobates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Such behaviors are unlikely to respond to environmental change and may result in incompetent sexual, social, or parental behavior in adulthood [Suomi, 1982]. Male gibbons that are raised by humans tend to exhibit neurotic behaviors [Kawakami and Kollias, 1984;Maxwell, 1984;Mootnick and Baker, 1994;Mootnick and Nadler, 1997], and the male in the present study was no exception. Exhibiting both thumb-sucking and masturbation directed toward humans, the LPZ male's aberrant behavior was consistent with behavior reported for other hand-reared gibbons.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Such behaviors are unlikely to respond to environmental change and may result in incompetent sexual, social, or parental behavior in adulthood [Suomi, 1982]. Male gibbons that are raised by humans tend to exhibit neurotic behaviors [Kawakami and Kollias, 1984;Maxwell, 1984;Mootnick and Baker, 1994;Mootnick and Nadler, 1997], and the male in the present study was no exception. Exhibiting both thumb-sucking and masturbation directed toward humans, the LPZ male's aberrant behavior was consistent with behavior reported for other hand-reared gibbons.…”
Section: Discussionmentioning
confidence: 71%
“…Exhibiting both thumb-sucking and masturbation directed toward humans, the LPZ male's aberrant behavior was consistent with behavior reported for other hand-reared gibbons. A study by Mootnick and Baker [1994] suggested that masturbation in captive adult male and female gibbons may be linked to early social experience, including social isolation from conspecifics during their youth. The authors suggested that gibbons experiencing such isolation may direct masturbation toward humans and be correspondingly less interested in conspecific sexual partners.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Observations of captive gibbons masturbating are few, with the notable exception of Mootnick and Baker (1994). These authors suggest that isolation from conspecifics during the early years of life may result in masturbation being directed towards humans, which may correlate with a tendency to be uninterested in Hylobates sexual partners.…”
Section: Human-directed Masturbationmentioning
confidence: 84%
“…Mootnick and Baker (1994) also suggest that gibbons with backgrounds of early conspecific isolation may be less suitable for captive breeding programmes. The Kalaweit gibbons have yet to produce any offspring, so more data are needed to further test this hypothesis.…”
Section: Discussionmentioning
confidence: 96%